Evaluasi Kebijakan Pengendalian Dan Pemberantasan Penyakit Hewan Menular Rabies Di Kabupaten Kapuas Hulu - Maryatiningsih Maryatiningsih; Sugito Sugito; Ahmad Tohardi (JPASDEV : Journal of Public Administration and Sociology of Development, 2020)
AbstractThe research problem lies in the low success rate of the policy for the control and eradication of rabies infectious animal disease. The research objectives are to evaluate and analyze the policy for the control and eradication of rabies infectious animal disease. The research method was conducted qualitatively through interviews, observation and documentation. The results indicate that the policy for the control and eradication of rabies infectious animal disease observed from the effectiveness, efficiency, responsiveness, equity and accuracy is considered to have quite good results in the context of rabies prevention. Implementation of socialization and vaccination is considered quite effective and efficient even though it has not clearly shown maximum results. However, there has been an increase in preventing rabies; this can be done according to established guidelines and the support of relevant stakeholders. The community basically has a good response to rabies control and eradication policy, especially that related to health. In the aspects of effectiveness, efficiency, responsiveness, equity and accuracy are considered quite optimal due to adequate support and availability of facilities and human resources. However, in terms of adequacy, it has not been fulfilled due to wide reach of the region and the large number of cases that occur as well as the limited budget. Socialization has been implemented in almost all sub-districts in Kapuas Hulu Regency, while vaccination in one sub-district is implemented in all villages up to the hamlet; this proves that the benefits of socialization and vaccination are sufficiently felt by the community. The community has been able to anticipate and take action/first aid if bitten by rabies-transmitting animals and immediately go to the nearest community health center to get an Anti-Rabies Vaccine. Overall, the policy for the control and eradication of rabies infectious animal disease is quite good although there are still areas that have not been reached. Therefore, there are areas that are still at risk of rabies because the mobile nature of rabies-transmitting animals, especially dogs. According to the evaluation theory of William M. Dunn, policy evaluation on for the control and eradiation of rabies infectious animal disease is considered effective in the aspect of Effectiveness, Efficiency, Equity, Responsiveness and Accuracy but it has not been considered effective in the aspect of Adequacy. Key words : Policy evaluation, Control and eradication, Rabies